Treatment with a fixed dose combination for cardiovascular disease-more than a health benefit?. (14th October 2021) - Dima, I; Andrikopoulos, G; Demerouti, E; Giannakoulas, G; Kartalis, A; Lambropoulos, K; Marketou, M; Papadopoulos, C; Poulimenos, L; Stalikas, D; Stougiannos, P; Tsiafoutis, I; et al.
Abstract: Background: Despite the proven benefits of cardiovascular disease medication, adherence to treatment remains poor. Fixed-dose combinations (FDC) have been proposed as a measure to enhance adherence. Objective: To assess compliance to treatment with an FDC, consisting of acetylsalicylic acid, atorvastatin and ramipril, and to gauge its impact on cardiovascular risk factors. Methods: This was a prospective, multicenter, observational, phase 4 study conducted for 6 months in Greece. 1444 participants (67% males, mean age 63.7 years old) that were prescribed the FDC for primary or secondary prevention were included in the analysis. Descriptive statistical analysis was performed to analyze clinical, sociodemographic and safety parameters. Results: Approximately equal number of participants was recruited in the primary and secondary prevention group. The majority of patients were overweight and hypertensive. Dosing compliance was 88.6% at 3 months and 86.8% at 6 months. Adherence to treatment was 99.1% at 3 months and 97.6% at 6 months. Statistically significant changes at 6 months compared to baseline were documented in systolic/diastolic blood pressure of 15.7/7.5 mmHg and LDL-c of 32.6 mg/dl, in both CVD and non-CVD participants and in total population as well. The total 10-year risk for CV events was reduced by 34.1% at 6 months. Only 1.2% of the participants reported an adverse event and 0.8% an adverse event reaction. Conclusions: Among patients with or without CVD, the use of acetylsalicylic acid, atorvastatin and ramipril FDC resulted in good medication adherence at 6 months and statistically significant improvements in blood pressure, total cholesterol and LDL levels. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Galenica SA